2022
DOI: 10.23971/jefl.v13i1.4496
|View full text |Cite
|
Sign up to set email alerts
|

“I can’t search on Google for answers”: validity evidence of a developed computer-based assessment application

Abstract: While learning management systems have been increasingly used as innovative ways to teach students in the post-COVID-19 pandemic, academic dishonesty is still in crisis. The open-access facility has the potential intervention in academic dishonesty. This study reported validity evidence of a developed computer-based assessment application to combat academic dishonesty: 1) measuring the development of high-order-thinking-skill (HOTS) test items; 2) examining the test item's validity integrated into the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(62 reference statements)
0
0
0
Order By: Relevance
“…Another element to analyze is that teaching a foreign language presents unique challenges, which can lead EFL students to resort to fraud due to linguistic competence issues, academic writing challenges, time limitations, and lack of confidence [ 34 ]. Finally, time constraints, inadequate paraphrasing skills, and pressure to achieve good grades [ 35 ], along with technological advancements and COVID-19, have heightened academic dishonesty [ [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another element to analyze is that teaching a foreign language presents unique challenges, which can lead EFL students to resort to fraud due to linguistic competence issues, academic writing challenges, time limitations, and lack of confidence [ 34 ]. Finally, time constraints, inadequate paraphrasing skills, and pressure to achieve good grades [ 35 ], along with technological advancements and COVID-19, have heightened academic dishonesty [ [41] , [42] , [43] , [44] , [45] ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nimasari et al in Indonesia identified distinct reasons for EFL students cheating, including lack of time, inadequate paraphrasing skills, and pressure to achieve good grades [ 35 ]. In the context of EFL, Saleh and Meccawy [ 36 ] found that female students in Saudi Arabia often cheated by assisting each other, copying answers from peers, or using electronic sources during exams.…”
Section: Introductionmentioning
confidence: 99%
“…This practice helps prevent staff members from feeling isolated and disconnected, while also providing an opportunity for teachers to interact with one another in a secure manner. By maintaining positive relationships and fostering collaboration, teachers can effectively adapt to the virtual learning environment without losing the essential connections they had before the shift (Nimasari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%